DEVELOPING A COMMUNICATIVE PLANNING APPROACH TO RESOLVE LAND USE CONFLICTS IN JELUTONG AREA OF GEORGETOWN, PENANG, MALAYSIA - Mohit, Mohammad Abdul; B.R.M Harun, Raja Mohd Firdous (PLANNING MALAYSIA, 2007)
This paper examines the urban land use conflict cases which have generated several environmental problems in a small area of Jelutong in Georgetown, Malaysia. Three cases of land use conflicts were identified in the area. The first case was the location of two industries adjacent to a residential area; the second involved the location of a factory within a river reserve area; and the third case was the location of a bus workshop within surrounding residential land uses. The conflicts of interest and spatial environmental implications of each of the conflict cases were analyzed. Based on the findings, the paper also identifies the reasons for the occurrence of those conflicts. Five alternative approaches were developed, with a recommendation to adopt a communicative approach (consensus building) to deal with the environmental problems and improve the living environment of the area.